Improving shacks, upgrading settlements: An ethnography of solar power infrastructure in the informal settlement of Enkanini, Stellenbosch - Visser, Christo (Stellenbosch : Stellenbosch University, 2017)
Thesis (MA)--Stellenbosch University, 2018.